Revision of the genus Disparomitus van der Weele, 1909 with descriptions of four new species (Neuroptera, Ascalaphidae) - Michel, Bruno (Zootaxa, 2019)
The genus Disparomitus van der Weele is revised and redescribed. Thirteen species are recorded: Disparomitus abyssinicus van der Weele, D. bacillus (Gerstaecker), D. brevistigma (Esben-Petersen), D. caviceps n. sp., D. citernii Navás, D. haullevillei (Navás) n. comb., D. kimminsi n. sp., D. lineatus n. sp., D. sellatus (Navás) n. comb., D. simplex Kimmins, D. spatula n. sp., D. transvaliensis (van der Weele) and D. yemenicus Hölzel. Disparomitus horvathi van der Weele and D. schoutedeni Navás are considered nomina dubia. The genera Nanomitus Navás and Nagacta Navás are synonymnized with Disparomitus. Nagacta leplaei Navás, N. schoutedeni Navás, Suphalacsa microstigma Navás and Disparomitus schultzei Esben-Petersen are considered as junior synonyms of D. haullevillei. D. longus Navás is considered a junior synonym of D. transvaliensis. Suphalasca subcostalis Navás is considered a junior synonym of D. bacillus. Disparomitus rufocostatus Esben-Petersen, D. maynei Navás and D. congoensis Navás are removed from the genus Disparomitus. All species placed in Disparomitus are illustrated. The distribution of the taxa as well as ecological and behavioral information are provided.